Neuropsychological analysis of a case with anosognosia - Gaibor-Estévez, Jhonny (2020)
Anosognosia is a neuropsychological disorder that generates in the patient an inability to have a state of full awareness about their disease or deficit due to brain injury. In this article we report the analysis of a case that, due to a head injury, presented this brain disorder. The neuropsychological analysis begins with the clinical description of the case, its premorbid status, the family report of the current state and a neuropsychological analysis of the symptoms presented that support the diagnostic hypothesis of anosognosia. The case presented is discussed based on the need to make accurate diagnoses and propose neuropsychological rehabilitation programs so that patients with anosognosia suffer the least possible impact on the activities of their daily lives as a result of acquired brain disorder. © 2020 Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.